Pathological basis of severe malaria in children: investigating immune dysregulation, organ-specific damage, and long-term outcomes - Shahid, Areeba; Oshingbesan, Mosunmade; Uchenna, Okafor Ugochukwu; Kansal, Gaurav; Sanan, Ahmad; Zubairu, Zainab Abdullahi; Tsalla, Tinggon Clifford; Egbo, Arube Ruby; Ozoemena, Davidson John; Ernest-Okonofua, Excel Onajite; Oduoye, Malik Olatunde; Nazir, Abubakar (International Journal Of Community Medicine And Public Health, 2025)
Malaria is a globally endemic parasitic disease, particularly prevalent in tropical regions and primarily affecting children and pregnant women. Comprehending the pathological mechanisms underlying severe malaria is crucial for enhancing treatment outcomes and decreasing mortality rates. This study aims to investigate immune dysregulation in severe malaria, explore organ-specific damage resulting from malaria infections in children, and examine long-term health consequences in survivors of severe malaria. This literature review involved an extensive literature search across electronic databases including PubMed, Google Scholar, Scopus, and Web of Science using keywords such as: severe malaria, children, immune dysregulation, organ-specific damage, and outcomes from 2015 to 2025. The study found cytokine imbalance and endothelial dysfunction due to immune dysregulation, liver and kidney dysfunction, and hematological changes due to severe malaria. To prevent the consequences of severe malaria in children, awareness and early detection of malaria signs and symptoms, next-generation sequencing, proteomics, and metabolomics, as well as regional and community-based malaria research, are required.